A World of Viruses Nested within Parasites: Unraveling Viral Diversity within Parasitic Flatworms (Platyhelminthes) - Nolwenn M. Dheilly; Pierrick Lucas; Yannick Blanchard; Karyna Rosario (Microbiology Spectrum, 2022)
ABSTRACT Because parasites have an inextricable relationship with their host, they have the potential to serve as viral reservoirs or facilitate virus host shifts. And yet, little is known about viruses infecting parasitic hosts except for blood-feeding arthropods that are well-known vectors of zoonotic viruses. Herein, we uncovered viruses of flatworms (phylum Platyhelminthes, group Neodermata) that specialize in parasitizing vertebrates and their ancestral free-living relatives. We discovered 115 novel viral sequences, including 1 in Macrostomorpha, 5 in Polycladida, 44 in Tricladida, 1 in Monogenea, 15 in Cestoda, and 49 in Trematoda, through data mining. The majority of newly identified viruses constitute novel families or genera. Phylogenetic analyses show that the virome of flatworms changed dramatically during the transition of neodermatans to a parasitic lifestyle. Most Neodermata viruses seem to codiversify with their host, with the exception of rhabdoviruses, which may switch hosts more often, based on phylogenetic relationships. Neodermata rhabdoviruses also have a position ancestral to vertebrate-associated rhabdo viruses, including lyssaviruses, suggesting that vertebrate-associated rhabdoviruses emerged from a flatworm rhabdovirus in a parasitized host. This study reveals an extensive diversity of viruses in Platyhelminthes and highlights the need to evaluate the role of viral infection in flatworm-associated diseases. IMPORTANCE Little is known about the diversity of parasite-associated viruses and how these viruses may impact parasite fitness, parasite-host interactions, and virus evolution. The discovery of over a hundred viruses associated with a range of free-living and parasitic flatworms, including parasites of economic and clinical relevance, allowed us to compare the viromes of flatworms with contrasting lifestyles. The results suggest that flatworms acquired novel viruses after their transition to a parasitic lifestyle and highlight the possibility that they acquired viruses from their hosts and vice versa. An interesting example is the discovery of flatworm rhabdoviruses that have a position ancestral to rabies viruses and other vertebrate-associated rhabdoviruses, demonstrating that flatworm-associated viruses have emerged in a vertebrate host at least once in history. Therefore, parasitic flatworms may play a role in virus diversity and emergence. The roles that parasite-infecting viruses play in parasite-associated diseases remain to be investigated.